The Influence of Humour on Learners’ Attitude and Mathematics Achievement: A Case of Secondary Schools in Arusha City, Tanzania - Ngussa, Baraka Manjale; Mbuti, Elias Elisha (IJRDO- Journal of Educational Research, 2017)
While there are many factors which can contribute to success or failure in Mathematicsachievement, teaching-learning strategy is an important factor which cannot be ignored. Thisstudy employed case study design to investigate the influence of humour as an instructionaltool on secondary school learners’ attitude and mathematics achievement in Arusha City,Tanzania. A sample of 412 Form Three students participated by filling the questionnaire.Expert judgment ensured that the questionnaire items provided useful information thatcorresponds to research questions. Reliability test for three variables yielded conbach’salpha between 0.73 and 0.79 meaning items in the questionnaire were reliable. Quantitativemethod in terms of descriptive statistics established mean scores while inferential statistics interms of t-test and Pearson Product moment corelational coefficient tested differences andrelationships respectively. The study concludes that the more the use of humour in teaching,the better the attitude and mathematics achievement. Therefore, it is recommended thatMathematics teachers should increase the use of humour while teaching in order to increaselearner’s interest in the subject matter and in that way improve performance